IMPLIKASI TEORI BELAJAR DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BAGI GENERASI DIGITAL - Silvia Isna Auladah Herman; Samsul Susilawati; Nurlaeli Fitriah (Al-Rabwah, 2026)
The development of digital technology in the 21st century has significantly transformed educational practices, including Islamic Religious Education (PAI). Digital generation learners possess unique learning characteristics, such as high digital literacy, preference for interactive media, collaborative learning tendencies, and critical thinking skills. These changes require educators to develop adaptive and contextual learning approaches based on appropriate learning theories. This article aims to analyze major learning theories, including behaviorism, cognitivism, constructivism, and humanism, and examine their implications for Islamic Religious Education learning among digital generation students. This study employed a library research method by reviewing various scientific references related to learning theories, digital-era learners, and Islamic education. The findings indicate that each learning theory contributes differently to PAI learning. Behaviorism supports habit formation and discipline, cognitivism strengthens conceptual understanding, constructivism promotes active and contextual learning, while humanism emphasizes character and spiritual development. The integration of these theories into digital learning media such as interactive quizzes, educational videos, collaborative platforms, and reflective digital content can create more meaningful, engaging, and relevant Islamic learning experiences for digital generation students.